Lonely castle in the mirror - Tsujimura, Mizuki, 1980- (Erewhon Books, 2022)
In Tokyo, seven students are hiding in their darkened bedrooms, unable to face their family and friends -- until the moment they find the mirrors in their bedrooms are shining. At a single touch, they are pulled from their lonely lives into to a wondrous castle straight out of a Grimm's fairy tale. As time passes, only those brave enough to share their stories will be saved. As they struggle to abide by the rules of the game, a moving story unfolds, of seven characters trapped in a cycle of misunderstanding and loneliness, who are ultimately set free by the power of friendship, empathy, and sacrifice.